Advances in business and management forecasting. Vol. 5 - Lawrence, Kenneth D.; Geurts, Michael D. (Emerald, 2008)
"Advances in Business and Management Forecasting" is a blind refereed serial publication published on an annual basis. The objective of this research annual is to present state-of-the-art studies in the application of forecasting methodologies to such areas as sales, marketing, and strategic decision making. (An accurate, robust forecast is critical to effective decision making.) It is the hope and direction of the research annual to become an applications and practitioner-oriented publication.The topics will normally include sales and marketing, forecasting, new product forecasting, judgmentally-based forecasting, the application of surveys to forecasting, forecasting for strategic business decisions, improvements in forecasting accuracy, and sales response models. It is both the hope and direction of the editorial board to stimulate the interest of the practitioners of forecasting to methods and techniques that are relevant. In Volume 5, there are sections devoted to financial applications of forecasting, as well as demand forecasting. There is, also, a section on general business applications of forecasting, as well as one on forecasting methodologies.It presents state-of-the-art studies in the application of forecasting methodologies to such areas as sales, marketing, and strategic decision making. It is published annually."
Keywords: Business forecasting.; Industrial management -- Forecasting.; elektronické knihy; electronic books